192k views
4 votes
Help??????? It’s precal

Help??????? It’s precal-example-1
User Atilla
by
5.2k points

2 Answers

4 votes

what does precal mean I don't understand

User Alireza Zojaji
by
5.5k points
7 votes
ANSWER


(F)/(G) ( - 1) = - ( 2)/( 3)

Step-by-step explanation

The given functions are:


F(x)=2x

and


G(x)= {x}^(2) + 2


(F)/(G) (x) = (F(x))/(G(x))


(F)/(G) (x) = \frac{2x}{ {x}^(2) + 2 }

Substitute x=-1


(F)/(G) ( - 1) = \frac{2( - 1)}{ {( - 1)}^(2) + 2 }


(F)/(G) ( - 1) = ( - 2)/( 1+ 2 )


(F)/(G) ( - 1) = - ( 2)/( 3)

The first choice is correct.
User Meric Ozcan
by
5.4k points